This preview shows page 1. Sign up to view the full content.
Unformatted text preview: ijk = ikj . We shall adopt Einsteins summation convention, that is repeated index implies summation. Lets look at the ith component of ( ), namely, ( ) i = ijk j ( ) k = ijk j k = 1 2 ( ijk + ijk ) j k = 1 2 ( ijk j k + ikj k j ) = 1 2 ( ijk j k  ijk j k ) = 0 . In the last but one step, we had made used of the fact that j and k are dummy variables, and the partial derivatives are interchangable, j k = k j . 1...
View Full
Document
 Fall '04
 POLLACK
 Physics, Magnetism

Click to edit the document details